2020
DOI: 10.1183/23120541.00017-2020
|View full text |Cite
|
Sign up to set email alerts
|

Low adherence to inhaled corticosteroids/long-acting β2-agonists and biologic treatment in severe asthmatics

Abstract: Eligibility criteria for a biologic treatment for severe asthma include poor disease control despite a full medication plan according to Global Initiative for Asthma steps 4-5 [1]. Adherence to inhaled therapy should be verified as part of that prescription requirement [2]. In fact, it has been demonstrated that poor adherence is a major cause of uncontrolled asthma, regardless of its severity [3]. Furthermore, biologics do not exert a disease-modifying effect [4]; in contrast to allergen immunotherapy, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 13 publications
1
8
0
1
Order By: Relevance
“…Although low treatment adherence was the only determinants of poorly controlled asthma, patients recruited in the present study showed a surprisingly high overall crude rate of treatment adherence (92%). This finding is quite unexpected, when considering the actual data from the Italian Medicine Agency (AIFA), which report an overall poor treatment adherence for asthma [27]. Furthermore, the adherence rate, when objectively evaluated, seems to be independent of the disease severity [28,29], so that the prevalence of patients with moderate and severe persistent asthma in our population cannot be truly considered a potential explanation for our observation.…”
Section: Discussionmentioning
confidence: 70%
“…Although low treatment adherence was the only determinants of poorly controlled asthma, patients recruited in the present study showed a surprisingly high overall crude rate of treatment adherence (92%). This finding is quite unexpected, when considering the actual data from the Italian Medicine Agency (AIFA), which report an overall poor treatment adherence for asthma [27]. Furthermore, the adherence rate, when objectively evaluated, seems to be independent of the disease severity [28,29], so that the prevalence of patients with moderate and severe persistent asthma in our population cannot be truly considered a potential explanation for our observation.…”
Section: Discussionmentioning
confidence: 70%
“…This nding is quite unexpected, when considering the actual data from the Italian Medicine Agency (AIFA), which report an overall poor treatment adherence for asthma [27]. Furthermore the adherence rate, when objectively evaluated, seems to be independent of the disease severity [28,29], so that the prevalence of patients with moderate and severe persistent asthma in our population cannot be truly considered a potential explanation for our observation. More likely it re ects the typical overestimation of patients when interviewed about their compliance with therapy, already reported in the open literature [26].…”
Section: Discussionmentioning
confidence: 75%
“…This nding is quite unexpected, when considering the actual data from the Italian Medicine Agency (AIFA), reporting an overall poor treatment adherence [27]. Furthermore, the adherence rate, when objectively evaluated, seems to be independent from the disease severity [28,29], so that the prevalence of patients with moderate to severe persistent asthma in our study population cannot be used to explain the above gure. More likely it may re ect the typical overestimation of patients when interviewed about their compliance with therapy, as already reported in the open literature [26].…”
Section: Discussionmentioning
confidence: 78%